The Role of Four-Wheeled Patrols at the Sabhara Unit to Prevent Motorized Theft Crime: Case of Sumedang Police Jurisdiction Area - Anugerah Tarigan (Advances in Police Science Research Journal, 2020)
Crime of motor vehicle theft is the most common crime in the Sumedang District Police. The high number of motor vehicle theft crimes is an important concern for Polri in preventive efforts to prevent the occurrence of motor vehicle theft crimes in the Sumedang District Police area. This is the background for conducting research related to the Role of the Four Wheeled Sabhara Patrol Unit in order to prevent the occurrence of criminal acts of motor vehicle theft in the Legal Area of ​​the Sumedang District Police. The formulation of the problem in this study is a description of the implementation of Sabhara four-wheeled patrols and what factors influence the implementation of Sabhara's four-wheeled patrols and efforts to increase the role of Sabhara's four-wheeled patrols in order to prevent the occurrence of criminal acts of motor vehicle theft in the Sumedang District Police jurisdiction. This study uses theories and concepts so that research can be well discussed, theories and concepts used are POAC management theory (planning, organizing, actuating, controlling) 6M theory (man, money, materials, machines, methods, markets) patrol concepts and concepts motor vehicle theft. The methodology used in this research is a qualitative approach. Data and information obtained through interviews, observations and study documents related to the problems that exist in research. This research has several factors that become obstacles in the implementation of four-wheeled patrols to prevent the occurrence of motor vehicle theft criminal acts, namely the lack of patrol members, limited fuel oil and schedules and activities that are not in accordance with procedures. The conclusion of this research is that the implementation of patrols must be maximized by overcoming the obstacles found during the implementation of patrols in order to prevent the occurrence of criminal acts of motor vehicle theft in the Sumedang region. Suggestions related to this research are to make better coordination with related agencies and to add personnel members and budget funds so that the implementation of patrols runs well.